Proteome analysis of snake venom toxins: pharmacological insights - Georgieva, Dessislava; Arni, Raghuvir K. [UNESP]; Betzel, Christian (Expert Reviews, 2008)
Snake venoms are an extremely rich source of pharmacologically active proteins with a considerable clinical and medical potential. To date, this potential has not been fully explored, mainly because of our incomplete knowledge of the venom proteome and the pharmacological properties of its components, in particular those devoid of enzymatic activity. This review summarizes the latest achievements in the determination of snake venom proteome, based primarily on the development of new strategies and techniques. Detailed knowledge of the venom toxin composition and biological properties of the protein constituents should provide the scaffold for the design of new more effective drugs for the treatment of the hemostatic system and heart disorders, inflammation, cancer and consequences of snake bites, as well as new tools for clinical diagnostic and assays of hemostatic parameters.
Keywords: pharmacological activity; proteomics; Snake venom; Toxin; venom protein family